1998
DOI: 10.1055/s-2007-979290
|View full text |Cite
|
Sign up to set email alerts
|

Personality Correlates of +/- Pindolol Induced Decreases in Prolactin

Abstract: The present study was conducted to investigate if personality traits can be usefully related to serotonergic vs. dopaminergic action of the 5-HT1a-antagonist +/- pindolol. Forty healthy male volunteers (aged between 20 and 30 years) were randomly assigned to a placebo or a +/- pindolol (30 mg, oral dose) group in a double blind trial. Blood samples were drawn and analyzed for PRL concentrations. In addition, the subjects completed questionnaires on personality. The results indicated that +/- pindolol decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Serotonin in limbic system pathways is generally associated with behavioral inhibition (Soubrie, 1986). Blunted serotonin reactivity to serotonin stimulants is characteristic in high sensation seekers (Depue, 1995;Hennig et al, 1998;Netter et al, 1996). Thus there is tentative emerging support for the biochemical/neurological theory of ImpSS.…”
Section: Biochemistrymentioning
confidence: 99%
“…Serotonin in limbic system pathways is generally associated with behavioral inhibition (Soubrie, 1986). Blunted serotonin reactivity to serotonin stimulants is characteristic in high sensation seekers (Depue, 1995;Hennig et al, 1998;Netter et al, 1996). Thus there is tentative emerging support for the biochemical/neurological theory of ImpSS.…”
Section: Biochemistrymentioning
confidence: 99%
“…There is already evidence for an involvement of 5-HT in mechanisms underlying impulsiveness and aggression. For example, studies with human volunteers found acute tryptophan depletion (ATD) to increase impulsive and aggressive behavior, although these effects seem to depend on individual differences in impulsive personality traits (Bjork et al, 2000;Marsh et al, 2002) and various studies also implicated a role of 5-HT in aggression and impulsivity (Hennig et al, 1998;Netter et al, 1999). Although 5-HT has been implicated in impulsiveness and forms of inhibitory control in rodents, the role of 5-HT in humans remains unclear till now.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is evidence from other studies with healthy volunteers suggesting that at least some aspects of serotonergic function may be related to hostility across a wide range of hostility scores [18]. Further, Hennig et al [19] found a blunted PRL decrease in response to pindolol in healthy volunteers. Thus, previous research has shown hostility to be associated with blunted increases and blunted decreases to serotonergic agents in different populations.…”
Section: Discussionmentioning
confidence: 95%